GAMBARAN KECERDASAN EMOSIONAL SISWA KELAS V SDN 144 PADAELO KECAMATAN PENRANG KABUPATEN WAJO - Sudarto Sudarto; Yusril Ihza Mahendra; Muhammad Idris Jafar (JOEL: Journal of Educational and Language Research, 2023)
This research is a qualitative research type that aims to describe the emotional quotient of the fifth grade students at SDN 144 Padaelo, Penrang District, Wajo Regency. The subjects in this study were on 6 students in class V at SDN 144 Padaelo, Penrang District, Wajo Regency. The data collection technique in this study was an interview technique and the data analysis techniques were: data reduction, data display and conclusions. Research results and conclusions: a description of the emotional intelligence of the Fifth Grade of students at SDN 144 Padaelo, Penrang District, Wajo Regency, based on ten indicators, it can be concluded that the students have had emotional quotien in terms of: recognizing their own emotions related to sadness, recognizing their own emotions related the self-confidence, being optimistic, focusing at the learning prcocess, accept the opinions of others, empathy. While on indicators: managing of the self-emotions in building relationships, managing emotions related to frustration, managing emotions related to the anger, building relationships if have experiencing problems, and establishing the students cooperation are said had not emotional quotiont yet